2017
DOI: 10.1007/s41894-017-0018-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and control of dental erosion by professionally applied treatment

Abstract: Dental erosion is a type of tooth wear that occurs when the tooth is exposed to acids. It can be prevented by elimination or reduction of the acid challenge. Prevention should also aim at the remineralization of softened enamel by the enhancement of saliva remineralizing function through the use of fluoride formulations. The use of professionally applied products for the prevention and control of dental erosion should be a part of an overall preventive management program that includes home management by the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…This appliance prevents direct contact between teeth and acid solutions. Furthermore, it was suggested that lining the mouth guard with any alkaline agents can help neutralize the acidic substance pooling inside it [ 34 ]. The use of fluoridated mouth rinses and toothpaste both decreased the odds of erosion (AOR = 0.61 and 0.78, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…This appliance prevents direct contact between teeth and acid solutions. Furthermore, it was suggested that lining the mouth guard with any alkaline agents can help neutralize the acidic substance pooling inside it [ 34 ]. The use of fluoridated mouth rinses and toothpaste both decreased the odds of erosion (AOR = 0.61 and 0.78, respectively).…”
Section: Discussionmentioning
confidence: 99%